Transcriptome profiling combined with network analysis deepens the understanding of immune response mechanisms in blood of pacific oyster Crassostrea gigas infected by Vibrio alginolyticus - Zhang, Enshuo; Dong, Luyao; Bao, Xiaokai; Yang, Xinyu; Li, Yuxin; Feng, Yanwei; Yang, Jianmin; Li, Zan; Wang, Weijun (Frontiers in Marine Science, 2022)
Mass mortalities of oysters during the summer have been reported for years. Among the biological factors causing oyster death in summer, Vibrio infection is considered to be the most important factor. Vibrio alginolyticus is one of the main pathogens causing oyster diseases. V. alginolyticus can cause disease and death of fish, shrimp, shellfish, and other aquatic products. Human infection with V. alginolyticus can also cause skin infections, external ear canal infections, and other diseases. Hemocytes in the blood of Crassostrea gigas resemble vertebrate macrophages and play an important role in the immune regulation of organisms. Therefore, it is of great significance to analyze the blood transcriptome to study the anti-pathogen mechanism of the C. gigas. In our study, we performed a transcriptome profile of gene expression on C. gigas infected with V. alginolyticus at 12 and 48 hours, and identified 2,494 and 1,165 differentially expressed genes (DEGs) at two sampling time points. Then, the functions of DEGs were identified using GO (Gene Ontology) and KEGG (Kyoto Encyclopedia of Genes and Genomes) functional enrichment analysis, revealing that there were multiple significantly enriched GO terms and KEGG signaling pathways related to immunity. And a protein-protein interaction (PPI) network was construct using DEGs enriched in significant enriched immune-related KEGG signaling pathways. At last, we screened and validated 12 key genes with multiple protein interaction numbers or involved in more KEGG signaling pathways, and verified their expression changes by quantitative RT-PCR (qRT-PCR). For the first time, we studied the immune defense mechanism of C. gigas blood based on protein-protein interaction network, which explains how C. gigas lacking specific immunity survive in a pathogen-rich environment. This research provides reference for solving the problem of high mortality of C. gigas and other mollusks in summer, and provides reference for the future production of some disease-resistant C. gigas.